Laparoscopic surgical correction of endometriosis improves fertility rates in infertile patients: a retrospective analysis of 119 cases - Parmar, Prakash; Kannar, Avani; Ghodasara, Rukesh; Patel, Sweta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Endometriosis is a common cause of infertility, affecting up to 50% of women with infertility. Surgery is a widely used treatment option for endometriosis, and the removal of endometriomas, nodules, and total posterior compartment peritonectomy has been shown to improve fertility rates in affected patients. The aim of the present study was to evaluate the role of laparoscopic surgical correction of endometriosis by removal of endometriomas, nodules, and total posterior compartment peritonectomy in improving rates of fertility in patients with endometriosis. Methods: A retrospective analysis of 119 patients who underwent laparoscopic surgical correction of endometriosis for infertility between May 2021 and April 2023 at Venus Women’s Hospital and IVF Center, Rajkot, India, was conducted. Inclusion criteria were documented endometriosis confirmed on Ultrasound and/or laparoscopy or accidentally detected during laparoscopy. All patients underwent laparoscopy for diagnosis confirmation. The primary outcome was pregnancy. Results: A total of 119 patients with endometriosis-related infertility were included in the study. Of the 119 patients who underwent laparoscopic surgical correction of endometriosis, 11 were lost to follow-up, leaving 108 patients for analysis. Of these, 76 patients (70.4%) conceived within one year of surgery. Of those who conceived, 34 (44.7%) did so spontaneously, without any medical treatments. A total of 42 patients (55.3%) conceived with ovulation induction only or ovulation induction with intrauterine insemination (IUI). Twenty-two patients (28.9%) underwent in vitro fertilization (IVF) and conceived, while 10 (13.2%) did not conceive with the first cycle of IVF and were still undergoing infertility treatment. The majority of patients (95%) reported relief of dysmenorrhea and dyspareunia after surgery. Conclusions: Study suggests that laparoscopic surgical correction of endometriosis by removal of endometriomas, nodules, and posterior peritonectomy can improve rates of fertility in patients with endometriosis-related infertility. The procedure was also found to be effective in relieving pain symptoms in most patients.